Discovering the Global Landscape of 3D Animation: A Bibliometric Analysis - Mohd Suki , Norbayah; Mohd Suki, Norazah; Ishak , Mohamed Mustafa; Ahmad, Rosliza; Sudin, Kamal Bahrin (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The purpose of this study is to conduct a bibliometric analysis of publications on 3D animation in the Scopus database. Microsoft Excel, VOSviewer for data visualisation, and Harzing's Publish or Perish for citation metrics and analysis were employed to conduct the bibliometric analysis. Data were analysed among a sample of 305 publications on 3D animation published between 1984 and 2021 available in the Scopus database. The bibliometric analysis reveals that the number of publications on 3D animation research has been constantly increasing since 2002. In 2020, the total number of documents published in 3D animation reached 29 articles. China was named the most active country in the field of 3D animation. A total of 888 researchers from 43 different countries and 31 different institutions published 3D animations in multiple languages, including multi-author collaboration. Computer Science and Engineering are the two disciplines that are most prominently represented in the study of 3D animation. The most active institutions that published key publications linked to 3D animation research were Universitas Diponegoro and the University of Sharjah. This research is unique and significant to contribute to advancing the body of knowledge on 3D animation to add value to the complexities of scientific narratives. Future research direction is also furnished.